The Influence of Health Education on the Level of Knowledge About Bullying Behavior at MTS Al-Amin Jayanti - Kholipah, Siti; Marseva, Eva; Rohmah, Meynur (Jurnal Riset Media Keperawatan, 2025)
Health education means changing the way a person or society behaves from being sick to being healthy or a process to increase knowledge and influence the ability to maintain health. Knowledge is closely related to education, and it is hoped that the higher a person's level of education, the wider their knowledge will be. Bullying is defined as aggressive or attacking actions carried out intentionally using an imbalance of power and strength by doing things such as hitting, kicking, pushing, spitting on, mocking, teasing, insulting and threatening other people. Objective: To determine the level of knowledge about bullying behavior before and after being given health education and to determine the effect before and after being given health education on the level of knowledge about bullying behavior at MTS Al-Amin Jayanti. The research method used is quantitative research with pre-experimental or experimental methods. In this research the sample technique used was the saturated sample method. This sampling method is where every member of the population is taken as a sample. The number of samples in this study was 100 respondents, namely students and students of class 8 MTS at Al-Amin Jayanti. This data analysis uses the Wilcoxon Test. Wilcoxon test, this aims to compare the mean value of one variable from two paired samples between two groups that are connected or related to each other. Based on the results of the Wilcoxon test, significant results were obtained at 0.000 < 0.05 so it can be concluded that Ha has an influence before and after education. health on the level of knowledge about bullying behavior at MTS Al-Amin Jayanti.